Implementasi Quantum Teaching dalam Gerak Tari Kreasi Kelas V Sekolah Dasar Negeri 19 Pontianak Utara - Aprilianti, Fitri (Jurnal Didaktika Pendidikan Dasar, 2022)
This study aims to identify and describe the problems of learning dance subjects in elementary schools. The lack of teacher understanding and the lack of infrastructure are obstacles to the creativity of students to master dance subject matter. Therefore, this study aims to describe the creative dance movement skills by applying the Quantum Teaching model to the fifth grade students of Sekolah Dasar Negeri 19 North Pontianak. The approach used in this research is a qualitative approach with the type of research is descriptive. In this study, the researcher as a research instrument is directly involved in activities that occur in the field. Apart from being a research instrument, the researcher is also a planner, implementer, data collector, analyzer and data reporter. The research location is Sekolah Dasar Negeri 19 North Pontianak. The results showed that the application of the Quantum Teaching approach to the dance movements created by the fifth grade students of Sekolah Dasar Negeri 19 Pontianak Utara was successful and was in accordance with the learning objectives. These results were observed when students demonstrated creative dance movements. Students who were previously unenthusiastic become enthusiastic after being placed in groups to take of learning dance in the class.